2013
DOI: 10.1111/imj.12256
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable risks for modifiable lifestyle factors and breast cancer in New Zealand women

Abstract: The most important primary preventive strategies to reduce the risk of breast cancer in New Zealand are lifestyle changes to reduce obesity, promoting regular physical activity (which may in turn reduce the prevalence of obesity), reducing HRT use and avoiding high alcohol intake. Strategies that encourage regular physical activity and reduce obesity could also have other benefits, such as reduced risks of cardiovascular disease and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…7 Regarding postmenopausal breast cancer, the individual PAF observed for MHT was within the range observed in the literature (2.4 to 19.4%). [6][7][8]11,39,40 The results suggested that a statistically significant number of postmenopausal breast cancer cases could be attributed to the recent use of MHT, restricted to a combination of systemic oestrogen with a progestagen. 17 The postmenopausal individual PAF observed for BMI was within the range noted in the literature (0.2 to 24.8%), 7-10,39-41 as were those for alcohol (27.6 to 9.1%), [6][7][8]10,40 age at menopause (5.9 to 14.5%) [6][7][8]11 and age at menarche (7.7 to 18.8%) [5][6][7][8] The postmenopausal PAF associated with family history of breast cancer was lower than previously published estimations (5.7 to 15.7%) [5][6][7][8][9]11 because of a lower prevalence of family history in our study population (up to 20.4% in the literature vs. 7.3% in our population) and lower relative risk estimates (1.49 to 6.29 in the literature vs. 1.37 and 1.50 among premenopausal and postmenopausal women in our analyses, see Tables 1 and 2).…”
Section: Literature Confrontationmentioning
confidence: 99%
“…7 Regarding postmenopausal breast cancer, the individual PAF observed for MHT was within the range observed in the literature (2.4 to 19.4%). [6][7][8]11,39,40 The results suggested that a statistically significant number of postmenopausal breast cancer cases could be attributed to the recent use of MHT, restricted to a combination of systemic oestrogen with a progestagen. 17 The postmenopausal individual PAF observed for BMI was within the range noted in the literature (0.2 to 24.8%), 7-10,39-41 as were those for alcohol (27.6 to 9.1%), [6][7][8]10,40 age at menopause (5.9 to 14.5%) [6][7][8]11 and age at menarche (7.7 to 18.8%) [5][6][7][8] The postmenopausal PAF associated with family history of breast cancer was lower than previously published estimations (5.7 to 15.7%) [5][6][7][8][9]11 because of a lower prevalence of family history in our study population (up to 20.4% in the literature vs. 7.3% in our population) and lower relative risk estimates (1.49 to 6.29 in the literature vs. 1.37 and 1.50 among premenopausal and postmenopausal women in our analyses, see Tables 1 and 2).…”
Section: Literature Confrontationmentioning
confidence: 99%
“…12 We used prevalence data from 2001 and cancer incidence data from 2010 to give a nominal latent period of about 10 years. To account for population ageing with time since exposure and the latent period, we used prevalence data for the age category that was 10 years younger than the corresponding cancer incidence age category (for example, cancer incidence in the 25-34 years age group in 2010 was attributed to insufficient physical activity in the [15][16][17][18][19][20][21][22][23][24] To estimate the proportion of people exercising at different levels, we first estimated the average total minutes individuals reporting each activity combination spent exercising per week (online supplementary file: Table S2). To do this, we assumed that people who reported two types of activity performed each for half the average duration for each activity and that those who reported all three types of activity performed each for one-third of the average duration.…”
Section: Exposure Prevalence Estimatesmentioning
confidence: 99%
“…We attributed 6.9% of the future breast cancer burden for postmenopausal women to any current MHT use. Comparison with previous PAF estimates (3.2%–27%) from different eras and countries is not meaningful because of (i) variation in the prevalence estimates, due to decline in MHT use following the publication of the Women's Health Initiative trial and other results around 2002; and (ii) variation in the hazard ratios, due to differences in the distribution of MHT composition and duration, with oestrogen‐progestogen MHT increasing breast cancer risk to a greater extent than oestrogen‐only MHT. We show for the first time that most of the MHT‐related future breast cancer burden is attributable to five or more years duration of use (6.4% out of 6.9%), with 4.0% of the burden avoidable by limiting use to less than 5 years; this is largely a consequence of a substantial proportion (79%) of MHT users being long term users.…”
Section: Discussionmentioning
confidence: 90%
“…42 We attributed 6.9% of the future breast cancer burden for postmenopausal women to any current MHT use. Comparison with previous PAF estimates (3.2%-27%) 6,9,13,14,19,23,24 from different eras and countries is not meaningful because of (i) variation in the prevalence estimates, due to decline in MHT use following the publication of the Women's Health BMI, body mass index; CI, confidence interval; HR, hazard ratio; MHT, menopausal hormone therapy; PAF, population attributable fraction; PR, prevalence. Note: some percentages do not add up to 100 because of rounding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation